The integration models of procurement management of hybrid projects in development of project-oriented enterprises - Morozov, Victor V.; Liubyma, Iuliia O. (НТУ "ХПІ", 2016)
The aspects of resource provision of project implementation in development of project-oriented organizations and its positioning on domestic and international markets are studied in the article. It significantly affects not only the results of projects` research, but also the sustenance and development of such organizations. For realization of stated tasks, the authors proposed several conceptual models that allow to combine the processes of project management and operational processes of the company and on this basis to create hybrid projects for efficient procurement of product components and resources for project portfolio.

У статті вивчаються аспекти ресурсного забезпечення реалізації проекту розвитку проектно-орієнтованих організацій, а так само їх позиціонування на внутрішньому і міжнародному ринках. Це суттєво впливає не тільки на результати досліджень проектів, але так само на розвиток таких організацій. Для реалізації поставлених завдань, автори запропонували кілька концептуальних моделей, які дозволяють об'єднати процеси управління проектами та операційні процеси компанії і на цій основі створити гібридні проекти для ефективного здійснення закупівель компонентів продукту і ресурсів для портфеля проектів.
Інтеграційна модель управління закупівлями для гібридних проектів у розвитку проектно-орієнтованих організацій
Keywords: nanobiotechnologies; project-oriented enterprises; procurement; project management model; нанотехнології; моделі управління проектом; операційні процеси компанії; гібридні проекти